Treatment for chemotherapy-induced peripheral neuropathy: A systematic review of randomized control trials - Wang, Chenkun; Chen, Si; Jiang, Weiwei (Frontiers in Pharmacology, 2022)
Purpose: Treatment of chemotherapy-induced peripheral neuropathy (CIPN) is challenging for clinicians, and many clinical trials and meta-analyses on CIPN are controversial. There are also few comparisons of the efficacy among drugs used to treat CIPN. Therefore, this systematic review aimed to study the efficacy of drugs in treating CIPN using existing randomized controlled trials. Methods: Electronic databases were searched for randomized controlled trials (RCTs) involving any pharmaceutical intervention and/or combination therapy of treating CIPN. Results: Seventeen RCTs investigating 16 drug categories, duloxetine, pregabalin, crocin, tetrodotoxin, venlafaxine, monosialotetrahexosyl ganglioside (GM1), lamotrigine, KA (ketamine and amitriptyline) cream, nortriptyline, amitriptyline, topical Citrullus colocynthis (bitter apple) oil, BAK (baclofen, amitriptyline hydrochloride, and ketamine) pluronic lecithin organogel, gabapentin, and acetyl l-carnitine (ALC), in the treatment of CIPN were retrieved. Many of the included RCTs consisted of small sample sizes and short follow-up periods. It was difficult to quantify due to the highly variable nature of outcome indicators. Conclusion: Duloxetine, venlafaxine, pregabalin, crocin, tetrodotoxin, and monosialotetrahexosyl ganglioside exhibited some beneficial effects in treating CIPN. Duloxetine, GM1, and crocin showed moderate benefits based on the evidence review, while lamotrigine, KA cream, nortriptyline, amitriptyline, and topical Citrullus colocynthis (bitter apple) oil were not beneficial. Further studies were necessary to confirm the efficacy of gabapentin in the treatment of CIPN because of the controversy of efficacy of gabapentin. Furthermore, BAK topicalcompound analgesic gel only had a tendency to improve the CIPN symptoms, but the difference was not statistically significant. ALC might result in worsening CIPN. Most studies were not of good quality because of small sample sizes. Therefore, standardized randomized controlled trials with large samples were needed to critically assess the effectiveness of these drugs in treating CIPN in the future.